2019
DOI: 10.1136/bmjopen-2018-024491
|View full text |Cite
|
Sign up to set email alerts
|

Impact of first and second eye cataract surgery on physical activity: a prospective study

Abstract: ObjectivesTo investigate the impact of first eye and second eye cataract surgery on the level of physical activity undertaken by older adults with bilateral cataract.DesignProspective cohort study.SettingThree public ophthalmology clinics in Western Australia.ParticipantsFifty-five older adults with bilateral cataract aged 55+ years, awaiting first eye cataract surgery.Outcome measuresThe primary outcome measure was participation in moderate leisure-time physical activity. The secondary outcomes were participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…It was not considered whether the participants had any other eye disease or they had had cataract surgery. Since cataract surgery is associated with higher PA 12 , future studies should also consider this aspect. As alcohol consumption was evaluated through a 9categories frequency question, it is recommended that future studies evaluate not only the frequency of consumption, but also the quantity and type of alcohol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was not considered whether the participants had any other eye disease or they had had cataract surgery. Since cataract surgery is associated with higher PA 12 , future studies should also consider this aspect. As alcohol consumption was evaluated through a 9categories frequency question, it is recommended that future studies evaluate not only the frequency of consumption, but also the quantity and type of alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another prospective study of 9113 diabetic working-aged adults residing in Australia found that more vigorous PA was independently associated with a reduced risk of cataract surgery 11 . In a prospective cohort study conducted also in Australia, it was found that first and second eye cataract surgery each independently increased participation in moderate intensity leisure-time PA 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Cataract surgery can also increase physical activity (Meuleners et al. 2019) and prevent falls (Brannan et al. 2003; Harwood et al.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one would expect more referrals to cataract surgeries at the time of AD diagnosis, particularly because visual impairment is associated with the deterioration of cognitive skills (Lin et al 2004;Roger & Langa 2010) and cataract surgery might improve cognitive functioning in persons with cognitive disorders (Tamura et al 2004). Cataract surgery can also increase physical activity (Meuleners et al 2019) and prevent falls (Brannan et al 2003;Harwood et al 2005;Feng et al 2018), even though there are also conflicting findings that it might increase risk of falls (Meuleners et al 2012;Meuleners et al 2014). We should identify persons who would benefit from surgery when their cognitive problems are still relatively mild.…”
Section: Discussionmentioning
confidence: 99%
“…13 In terms of physical activity, a similar theme emerges in that cataract surgery improves moderate physical activity levels, but there were no changes in some activities, such as walking and gardening, and a trend towards decreased vigorous physical activity (p = 0.07) after first-eye surgery, that the authors felt might have been due to the unbalanced nature of vision and refractive correction after first-eye surgery. 15 Given the variable evidence in the literature regarding the impact of surgery on everyday activities, the purpose of this study was to explore individual patient experiences in adapting to their changing vision following cataract surgery. To identify any adaptation difficulties post-cataract surgery, we organised a series of focus groups with patients who had recently had cataract surgery and discussed their experiences of adaptations to the surgery in the short and medium term, including their adaptations to any new spectacles.…”
Section: Introductionmentioning
confidence: 99%